Identifikasi Kawasan Rawan Longsor di Banjarsari, Purwoharjo, Kulon Progo Menggunakan Metode HVSR dan Vs30 - Sunardi, Bambang; Kartiko, Ilham Bayu (Jurnal Stasiun Geofisika Sleman, 2024)
Landslides are processes involving the downward movement of material, such as rocks or soil, influenced by topographical, geological, and soil characteristics. The Banjarsari, Purwoharjo areas have been identified as having a high potential for landslide hazards due to their diverse and vulnerable soil conditions. This study utilized microtremor data analyzed using the HVSR and Vs30 methods to conduct microzonation to identify areas with a high potential for landslides. Key parameters analyzed include dominant frequency (f0), amplification (A0), seismic vulnerability index (Kg), peak ground acceleration (PGA), average shear wave velocity (Vs30), ground shear strain (GSS), and slope gradient. The analysis also involved a comparison of the Vs30 values obtained in this study with the USGS reference values. The microzonation results indicate that locations 2, 3, and 4 have the highest landslide vulnerability levels compared to other areas. These findings provide a critical basis for landslide disaster mitigation planning in the Banjarsari, Purwoharjo regions and serve as a reference for geophysics-based disaster risk management.